TINGKAT KEMANDIRIAN BELAJAR MAHASISWA DALAM PEMBELAJARAN DARING - Nur Fatah Abidin; Ghufronudin Ghufronudin; Bagas Narendra Parahita; Anis Suryaningsih; Lies Nurhaini (Jurnal Pendidikan, 2022)
The success of online learning implementation in higher education is determined by internal factor such as student self-directedness. The article aimed to measure students’ self-directedness in higher education context. The research respondents were 472 students from the Faculty of Teacher Training and Education, Sebelas Maret University. The respondent were selected based on cluster and random sampling. The data were collected through the Self-rating Scale of Self-Directed Learning (SRSSDL). The results showed the level of student learning self-directed learning is at a medium and high level. The results also illustrate the transformative ability of students in the setting of online learning. Overall, this study shows the importance of student self-direction in supporting online learning readiness. Therefore, teacher must be able to provide constructivism-based learning strategies and student-centred approaches that can accommodate student independence in the learning process.